Bioassay assessment of metarhizium anisopliae (metchnikoff) sorokin (deuteromycota: hyphomycetes) against Oncometopia facialis (signoret) (hemiptera: cicadellidae) - Pria Júnior, Wolney Dalla [UNESP]; Lacava, Paulo Teixeira; Messias, Claudio Luiz; Azevedo, João Lúcio; Lacava, Pedro Magalhães [UNESP] (Sociedade Brasileira de Microbiologia, 2008)
A Clorose Variegada dos Citros (CVC) é uma doença economicamente importante e destrutiva no Brasil e é causada pela bactéria Xylella fastidiosa e transmitida por insetos vetores tal como Oncometopia facialis. Nesse estudo, a eficácia do fungo Metarhizium anisopliae em controlar o inseto vetor O. facialis foi estudada em condições de bioensaio. Nesse bioensaio, insetos foram pulverizados com uma suspensão de 5 X 10(7) conídio mL-1. Insetos-adultos capturados no campo foram tratados em grupos de 10, em um total de 11 replicatas por tratamento. Diferenças significativas entre a mortalidade natural e a mortalidade dos insetos tratados com o fungo foram observadas em 6 dias após a inoculação (P<0.05). Estas diferenças significativas aumentaram antes do décimo dia após o tratamento. O fungo causou uma mortalidade de 87,1%, com uma LT50 variando entre 5 e 6 dias. A LC50 foi de 1,2 X 10(6) conídio mL-1, variando de 7,7 X 10(5) a 2 X 10(6) conídio mL-1. Estes resultados mostraram que o vetor O. facialis foi susceptível a ação entomopatogênica de M. anisopliae em condições controladas durante o bioensaio.

Citrus Variegated Chlorosis (CVC) is an economically important, destructive disease in Brazil and is caused by Xylella fastidiosa and transmitted by sharpshooter insects. In this study, the efficacy of the fungus Metarhizium anisopliae in controlling the sharpshooter Oncometopia facialis was studied by bioassay conditions. In the bioassay, insects were sprayed with a suspension containing 5 X 10(7) conidia mL-1. Adults captured in the field were treated in groups of 10 in a total of 11 replications per treatment. Significant differences between the natural mortality and the mortality of insects treated with the fungus were observed 6 days after inoculations (P<0.05). These significant differences increased until 10 days after treatment. The fungus caused 87.1% mortality, with the LT50 varying from 5 to 6 days. The LC50 was 1.2 X 10(6) conidia mL-1, varying from 7.7 X 10(5) to 2 X 10(6) conidia mL-1. The results showed that the sharpshooter O. facialis was susceptible to the entomopathogenic action of M. anisopliae in controlled condition during bioassay.
Avaliação do bioensaio de Metarhizium anisopliae (metchnikoff) sorokin (deuteromycota: hyphomycetes) contra Oncometopia facialis (signoret) (hemiptera: cicadellidae)
Keywords: controle microbiano; entomopatógeno; Clorose Variegada dos Citros (CVC); bioensaio; microbial control; entomopathogen; Citrus Variegated Chlorosis (CVC); bioassay